Real World Overall Survival of Patients With Metastatic Renal Cell Carcinoma Treated With Only Available Sunitinib and Pazopanib in First-Line Setting - Nikic, Predrag; Babovic, Nada; Dzamic, Zoran; Salma, Svetlana; Stojanovic, Vesna; Matkovic, Suzana; Pejcic, Zoran; Juskic, Kristina; Soldatovic, Ivan (Frontiers in Oncology, 2022)
Background The emerging new standard of care for metastatic clear cell renal carcinoma (mRCC) becomes a challenge when access to new drugs is limited. In Serbia, sunitinib and pazopanib are the only available first-line therapies. The second-line treatment for mRCC has never been and is still not available. We aimed to assess overall survival (OS) in patients with mRCC who received first-line sunitinib or pazopanib when access to second-line treatment was not available. Methods This retrospective observational study analyzed data from a nationally representative cohort of 759 patients who started on first-line sunitinib or pazopanib between 1 January 2012 and 30 June 2019, in 4 centers in Serbia. The data cut-off date was 31 December 2019. Key eligibility criteria were clear cell RCC histology, measurable metastatic disease, performance status 0 or 1, and the Memorial Sloan Kettering Cancer Center favorable or intermediate prognosis. The primary outcome was OS from the start of first-line treatment to death or data cut-off date. Results The study population included 759 patients with mRCC who started with first-line sunitinib (n = 673; [88.7%]) or pazopanib (n = 86; [11.3%]). Overall, the mean age was 61.0 ± 9.7 years at treatment baseline, and 547 (72%) were men. mRCC was primarily diagnosed in 230 (30%) patients, and most of them underwent cytoreductive nephrectomy prior to systemic therapy (n = 181 [79%]). Additional treatment of metastases prior to and/or during treatment was used in 169 patients (22.3%). Grade 3 and 4 adverse events occurred in 168 (22.1%) and 47 patients (6.2%), respectively, and treatment was permanently stopped because of toxicity in 41 (6.9%). The OS was calculated from the start of first-line treatment, and the median follow-up was 14 months (range, 0–97). The median OS in the entire cohort was 17 months (95% CI, 14.6–19.4). Conclusions With only available sunitinib and pazopanib in first-line treatment, modest improvements are seen in the overall survival of patients with mRCC in real world clinical practice. In circumstances of limited availability of cancer medicines, our results can contribute to accelerating patient access to novel cancer therapies that have been shown to prolong survival in mRCC.